DUKUNGAN MESIR TERHADAP PERJUANGAN KEMERDEKAAN PALESTINA 2011-2013 - Iskandar "; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study illustrates Egypt's foreign policy , particularly in view of the struggle for Palestinian independence . Since Muhammad Mursi served as President of Egypt Egypt's foreign policy towards more pro towards the Arab and Islamic world especially those of the Palestinians . Unlike the previous President Husni Mubarok more pro Israel and the West . During Mursi led the Egyptians many policies taken Mursi in support of the Palestinian struggle for independenceThis study uses a constructivist paradigm strengthened with the theory of foreign policy . That the measures taken of a country can not be separated from national interests and become the rationale for the decision. The method used in this study is a qualitative research method .Based on information from various sources that the authors get , seeing that the foreign policy of Egypt in support of the Palestinian struggle for independence caused the closeness of ideology between the Muslim Brotherhood in Egypt with Hamas in Palestine . So it is natural that Egypt was really supports Palestinian Ideology because closeness between the two countries .Keywords : Muslim Brotherhood , Hamas , Foreign Policy , Ideology , Organization